Ethnoscience exploration of sago processing as a science learning resource for elementary school - Indah Slamet Budiarti; Kusdianto Kusdianto; Megawati Megawati (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: The integration of local wisdom into science learning is crucial to promote contextual and meaningful education, particularly in primary schools. Despite its importance, the use of ethnoscience in primary school science curricula remains underexplored, leading to a disconnect between abstract scientific concepts and students' everyday experiences.Aim: This study aims to explore the ethnoscience of sago processing in Sarmi Regency, Papua, and its application as a science learning resource for elementary schools.Method: A qualitative descriptive method with a case study approach was employed, involving data collection through observations, interviews, and documentation with local community participants.Results: The results reveal that traditional sago processing encompasses basic scientific principles, including simple machinery, energy transfer, friction, and sedimentation, which can be effectively contextualized in science lessons.Conclusion: The integration of sago processing into the curriculum enhances students' comprehension of scientific concepts, fosters cultural appreciation, and encourages sustainability. These findings underscore the need to incorporate local wisdom into educational practices to develop student-centered, culturally relevant, and sustainability-oriented learning environments.